Evaluation of the Relationship Between the Severity of the Disease, the Neutrophil/Lymphocyte Ratio and CRP in Children with Bronchiolitis - Ömer Güneş; Meltem Erol; Özlem Bostan Gayret; Abdulrahman Özel; Övgü Büke (Bagcilar Medical Bulletin, 2021)

(untitled)
Objective:In this study, we aimed to evaluate the relationship among neutrophil-lymphocyte ratio (NLR), C-reactive protein (CRP) and disease severity in 0-2-year-old children diagnosed and hospitalized with bronchiolitis.Method:This retrospective cross-sectional study includes 158 patients aged 0-2 years, who were hospitalized for bronchiolitis between 01.12.2018 and 04.01.2020 in University of Health Sciences Turkey, İstanbul Bağcılar Training and Research Hospital’s Pediatrics Clinic. Patients’ age, gender, laboratory results and disease severity scores were recorded. According to this, disease severity was categorized as mild, moderate and severe.Results:No statistically significant difference was observed among the scores of disease severity, mean age of the groups and gender distribution (p=0.061, p=0.392). However, a statistically significant difference was found between the disease severity score and the neutrophil/lymphocyte (N/L) ratios (p=0.007). The N/L ratio of the “mild” group was seen as statistically significantly lower than that of the “moderate” and “severe” groups (p=0.003, p=0.006). No statistically significant correlation was detected among the disease severity score, mean age of the moderate and severe groups (r=0.081 p=0.311). A statistically significant difference was witnessed between the disease severity score and CRP values (p=0.014). The CRP values of the group with mild disease were realized to be significantly lower than that of the group with moderate severity (p=0.04).Conclusion:An increase in the NLR along with CRP is associated with the clinical severity and is a beneficial parameter that can be used for evaluating the prognosis of 0-2-year-old hospitalized patients with bronchiolitis.